The Influence of Primary Stakeholder, Secondary Stakeholder, and Regulatory Stakeholder on Carbon Emission Disclosure - Fina Dwi Nuriyani; R. Rosiyana Dewi (International Journal of Social Service and Research (IJSSR), 2023)
This research aims to analyze about direct and indirect influence between internal primary stakeholders, external primary stakeholders, secondary stakeholders and regulatory stakeholders on carbon emissions disclosure. The population of this research are non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 period. The sample in this research was 196 samples with purposive sampling method. The type of data in this study is secondary data, and panel data regression analysis with the eviews 10. The results of this research showed that investor-oriented industry, industry close to consumers, media exposure, and government pressure have a positive effect on carbon emission disclosure. Meanwhile employee-oriented industries and creditor pressure have a negative effect on carbon emission disclosure. Environmentally sensitive industries and the audit by KAP Big 4 had no influence on carbon emissions disclosure.